Development of FRID based 2d localization simulation for autonomous guided vehicle tracking in indoor environment - Al Hazza, Muataz Hazza Faizi; Zainal, Nur Izzati Zainal; Rodzi, Mohd Zuhaili Mohd (IAEME Publication, 2018)
The fast pace of technological development urges manufacturers to upgrade their systems to compete with the current industry. Autonomous Guided Vehicle (AGV) is one of the recent trends in the manufacturing. It promotes high efficiency and reduces labor cost to the manufacturer. As an enhancement feature for the AGV, in this paper, simulation of 2D localization for tracking an autonomous guided vehicle (AGV) using RFID in an indoor manufacturing environment is presented. The localization techniques are based on measuring the distance using path loss model from RSSI values provided by RFID and coordinates calculation using trilateration algorithm with multiple reference points. The mathematical process is coded in a software to produce a graphical user interface (GUI) based simulation for 2D localization of AGV tracking in indoor environment. Based from the data collected, the results show that the distance is computed experimentally and theoretically resulted average errors of 4.00 % and the AGV locations is measured from the calculated distance using trilateration algorithm. Therefore, the simulation can be enhanced for real time 2D localization of AGV tracking in indoor environment.